Anti-obesity effect of n-3 polyunsaturated fatty acids in mice fed high-fat diet is independent of cold-induced thermogenesis - Janovská, Petra; Flachs, Pavel; Kazdová, Ludmila; Kopecký, Jan (Physiological research, 2013)
Long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) exert beneficial effects on health and they could help to prevent development of obesity and associated metabolic disorders. In our previous studies in mice fed high-fat (cHF; ~60 % calories as fat) diet and maintained at 20 °C, dietary LC n-3 PUFA could counteract accretion of body fat, without inducing mitochondrial uncoupling protein 1 (UCP1) in adipose tissue, suggesting that the anti-obesity effect was not linked to adaptive (UCP1-mediated) thermogenesis. To exclude a possible dependence of the anti-obesity effect on any mechanism inducible by cold, experiments were repeated in mice maintained at thermoneutrality (30 °C). Male C57BL/6J mice were fed either cHF diet, or cHF diet supplemented with LC n-3 PUFA, or standard diet for 7 months. Similarly as at 20 °C, the LC n-3 PUFA supplementation reduced accumulation of body fat, preserved lipid and glucose homeostasis, and induced fatty acid re-esterification in epididymal white adipose tissue. Food consumption was not affected by LC n-3 PUFA intake. Our results demonstrated anti-obesity metabolic effect of LC n-3 PUFA, independent of cold-induced thermogenesis and they suggested that induction of fatty acid re-esterification creating a substrate cycle in white fat, which results in energy expenditure, could contribute to the anti-obesity effect.
Keywords: Animals; homeostáza; Fatty Acids, Omega-3; glukózový toleranční test; termogeneze; triglyceridy; Diet, High-Fat; Obesity; Fatty Acids, Nonesterified; Triglycerides; Glucose Tolerance Test; Mice; Homeostasis; látky proti obezitě; myši; Cold Temperature; Anti-Obesity Agents; omega-3 mastné kyseliny; tělesná hmotnost; Thermogenesis; obezita; Calorimetry, Indirect; Male; kyseliny mastné neesterifikované; Body Weight; zvířata; tuková tkáň; mužské pohlaví; nízká teplota; Mice, Inbred C57BL; dieta s vysokým obsahem tuků; nepřímá kalorimetrie; myši inbrední C57BL; Adipose Tissue